Age‐distributed composition of the Indigenous population in Australia. Issue 7 (31st May 2022) - Shankar, Sriram
Abstract: The standard measure of composition of a group within a country or a region is its headcount relative to the overall population. However, the headcount ratio of a given group ignores the age‐based variability of its population with respect to the whole population. In this paper, a measure capturing the groups' age‐wise distribution is proposed, which can be useful for policymakers in identifying potential demographic distortions experienced by population subgroups. An empirical exercise on the Australian Census data for the years 2006, 2011 and 2016 provides the age‐distributed composition of the Indigenous population in the states and territories of Australia.